Self-Care Recommendations of Middle-Aged and Older Adults with Sickle Cell Disease - Coretta M. Jenerette; Cheryl Brewer; Ashley N. Leak (Hindawi Limited, 2011)
Self-care management is an important part of living with a chronic illness. Sickle cell disease (SCD) is a chronic disease with acute, painful exacerbations that often results in a shortened life expectancy. Some middle-aged and older adults with SCD lived with the disease prior to having a diagnosis and without modern advances. The purpose of this study is to share the self-care recommendations of middle-aged and older adults with SCD. Using descriptive qualitative methods, data were gathered through semistructured interviews from 11 individuals living with SCD, including 6 women and 5 men. Self-care recommendations themes included physiological, psychological, and provider-related. The self-care recommendations may be seen as an additional resource or "words of wisdom" for younger adults with SCD who can use the recommendations to better manage their own disease. Additionally, providers may be able to use these recommendations to inform their practice.